1982
DOI: 10.1002/ecja.4410650208
|View full text |Cite
|
Sign up to set email alerts
|

Arc‐fusion splice of multimode optical fibers using pre‐fusion method

Abstract: In optical fiber splicing, the fusion technique using gas discharge heating is considered a practical method from the viewpoints of operation and reliability. The fusion by which the splicing is made after pre‐shaping by a gas discharge on the optical fiber ends, has excellent features of low loss and stable splices. However, the splicing mechanism and the optimum splicing condition have not yet been analyzed sufficiently. This paper studies splicing conditions such as the pre‐fusion time, optical fiber stuffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…To obtain a stable fiber end fixed in the holder, the length of the V groove is required to be 3 mm; and, therefore, the length of the fixed end becomes 3 mm. In arc fusion splicing, the required fixed end separation is reported to be about 5 mm [9]. Further, in this method, concerning the linked part, the fusion splicing with shielded heating in relation to the intensity distribution has been investigated; and it is reported that the separation between the ends can be as short as 1.5 mm [lo].…”
Section: Fiber Lengths Taking Into Account Their Vibrations and Fusiomentioning
confidence: 99%
“…To obtain a stable fiber end fixed in the holder, the length of the V groove is required to be 3 mm; and, therefore, the length of the fixed end becomes 3 mm. In arc fusion splicing, the required fixed end separation is reported to be about 5 mm [9]. Further, in this method, concerning the linked part, the fusion splicing with shielded heating in relation to the intensity distribution has been investigated; and it is reported that the separation between the ends can be as short as 1.5 mm [lo].…”
Section: Fiber Lengths Taking Into Account Their Vibrations and Fusiomentioning
confidence: 99%